Molecular-Based Strategies to Exploit the Inorganic Phosphate-Solubilization Ability of Pseudomonas in Sustainable Agriculture - Browne, P.; Barret, M.; Morrissey, J.; O'Gara, Fergal (John Wiley & Sons, 2013)
Modern agriculture is heavily dependent on the application of chemical inputs, including fertilizers and pesticides. Because of concerns regarding economics, human health, and environmental protection, viable alternatives to these chemicals are being sought. The exploitation of specific rhizosphere microorganisms as biofertilizers and biopesticides has the potential to improve plant growth and/or to reduce the incidence of soilborne disease. Pseudomonas spp., in particular, are known to exhibit multiple plant-growth-promoting characteristics involved in biocontrol and biofertilization. Previous work based on both culture-dependent and culture-independent approaches showed that different agricultural practices can lead to changes in the composition of Pseudomonas population at both the phylogenetic and functional levels. These studies have suggested that there is potential for the manipulation of agricultural strategies such as crop rotation, crop type, and fertilizer input to develop favorable microbial communities, including Pseudomonas, at the phylogenetic and functional levels. In this chapter, current knowledge regarding the potential contribution of Pseudomonas spp. in soil phosphate cycling is summarized.